2004
DOI: 10.1111/j.1469-0691.2004.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ciprofloxacin resistance and extended-spectrum β-lactamase production in Escherichia coli and Klebsiella pneumoniae strains

Abstract: Resistance to fluoroquinolones has increased markedly since their introduction. Mechanisms of resistance to any antibiotic class might play a role in resistance to an unrelated antibiotic class. This study evaluated the relationship between extended-spectrum beta-lactamase (ESBL) production and ciprofloxacin resistance in Escherichia coli and Klebsiella pneumoniae strains isolated as causative agents of urinary tract infection. ESBL-producing strains were significantly more frequent among ciprofloxacin-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 11 publications
7
28
0
3
Order By: Relevance
“…The ESBL-producing strains, in the present study, were coresistant to ciprofloxacin, which was in accordance to the report by Tolun et al (18). The study by Paterson et al (13) showed that 11 of the 15 ciprofloxacin-resistant ESBL-producing Klebsiella pneumoniae isolates belonged to just four genotypes, similarly 15 of the 18 ciprofloxacin-resistant ESBL-producing E. coli isolates in the present study were grouped into only two clones, suggesting that patient-to-patient transmission of such strains occurred.…”
supporting
confidence: 82%
“…The ESBL-producing strains, in the present study, were coresistant to ciprofloxacin, which was in accordance to the report by Tolun et al (18). The study by Paterson et al (13) showed that 11 of the 15 ciprofloxacin-resistant ESBL-producing Klebsiella pneumoniae isolates belonged to just four genotypes, similarly 15 of the 18 ciprofloxacin-resistant ESBL-producing E. coli isolates in the present study were grouped into only two clones, suggesting that patient-to-patient transmission of such strains occurred.…”
supporting
confidence: 82%
“…Fluoroquinolone resistance is becoming a common feature rather than an exception in ESBL-producing isolates (43,37,46,39). In our study, the decrease in the rate of fluoroquinolone susceptibility was high both in the community (62.5%) and in the hospital (41.6%) isolates recovered from patients during 2003 (Table 3).…”
Section: Vol 42 2004 Fecal Carrriage Of Esbl-producing Isolates 4771mentioning
confidence: 75%
“…Klebsiella spp a aussi affiché une résistance de 4,23% à 94,64% aux aminosides, 75% à 95,83% aux quinolones. Ces observations corroborent les travaux de Tolun et al (2004). Selon certains auteurs, le plasmide qui porte le gène de résistance aux bêta-lactamines porterait également le gène QnrA de résistance aux quinolones (Bradford, 2001 ;Paterson et Bonomo, 2005); ce fait expliquerait bien mieux la multirésistance de certaines souches EBLSE.…”
Section: Materiel Et Methodesunclassified